A cohort study of early neurological consultation by telemedicine on the care of neurological inpatients. Issue 7 (16th June 2004) - Craig, J; Chua, R; Russell, C; Wootton, R; Chant, D; Patterson, V
Abstract : Objectives: To find out the effect of early neurological consultation using a real time video link on the care of patients with neurological symptoms admitted to hospitals without neurologists on site. Methods: A cohort study was performed in two small rural hospitals: Tyrone County Hospital (TCH), Omagh, and Erne Hospital, Enniskillen. All patients over 12 years of age who had been admitted because of neurological symptoms, over a 24 week period, to either hospital were studied. Patients admitted to TCH, in addition to receiving usual care, were offered a neurological consultation with a neurologist 120 km away at the Neurology Department of the Royal Victoria Hospital, Belfast, using a real time video link. The main outcome measure was length of hospital stay; change of diagnosis, mortality at 3 months, inpatient investigation, and transfer rate and use of healthcare resources within 3 months of admission were also studied. Results: Hospital stay was significantly shorter for those admitted to TCH (hazard ratio 1.13; approximate 95% CI 1.003 to 1.282; p = 0.045). No patients diagnosed by the neurologist using the video link subsequently had their diagnosis changed at follow up. There was no difference in overall mortality between the groups. There were no differences in the use of inpatient hospital resources and medical services in the follow up period between TCH and Erne patients. Conclusions: Early neurological assessment reduces hospital stay for patients with neurological conditions outside of neurological centres. This can be achieved safely at a distance using a real time video link.